2007
DOI: 10.1111/j.1600-0447.2007.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnoses in young offspring from eastern Québec multigenerational families densely affected by schizophrenia or bipolar disorder

Abstract: . Clinical diagnoses in young offspring from eastern Que´bec multigenerational families densely affected by schizophrenia or bipolar disorder.Objective: The follow-up since 1989 of a large sample of multigenerational families of eastern Que´bec that are densely affected by schizophrenia (SZ) or bipolar disorder (BP) has permitted to look at the rates of DSM diagnoses in the young offspring of a SZ parent (HRSZ) and of a BP parent (HRBP) who had an extremely loaded family history. Method: The sample (average ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 45 publications
(83 reference statements)
7
41
2
5
Order By: Relevance
“…Although family studies suggest little co-aggregation of SZ and BP, 1 an observable trend is that many of the genetic vulnerability loci may be shared by SZ and BP, which challenges the traditional Kraepelinian dichotomy and current nosology. 2 -8 This trend is congruent with the observations that BP and SZ share early in life, 9,10 and later on, 11,12 several phenotypic features encompassing the neurobiological, neuropsychological and clinical domains. Seemingly in contrast with the evidence of genetic influences crossing the SZ and BP DSM boundaries, a second emerging pattern of findings suggests distinct subgroups within the SZ or within the BP diagnosis, such as the negative symptoms and of SZ found associated with a 6p locus, 13,14 or the psychotic BP subtype with a 16p locus or 13q21 -q33.…”
Section: Introductionsupporting
confidence: 73%
“…Although family studies suggest little co-aggregation of SZ and BP, 1 an observable trend is that many of the genetic vulnerability loci may be shared by SZ and BP, which challenges the traditional Kraepelinian dichotomy and current nosology. 2 -8 This trend is congruent with the observations that BP and SZ share early in life, 9,10 and later on, 11,12 several phenotypic features encompassing the neurobiological, neuropsychological and clinical domains. Seemingly in contrast with the evidence of genetic influences crossing the SZ and BP DSM boundaries, a second emerging pattern of findings suggests distinct subgroups within the SZ or within the BP diagnosis, such as the negative symptoms and of SZ found associated with a 6p locus, 13,14 or the psychotic BP subtype with a 16p locus or 13q21 -q33.…”
Section: Introductionsupporting
confidence: 73%
“…10,44,45 Granted there are intermediate clinical presentations and reports of overlapping genetic and neurobiological findings; however, in part this reflects the broadening of the BD concept 20,46 and assortative mating. 47,48 Another challenge to the proposal of simply generalizing the early psychosis model to mood disorders is that BD is not diagnosed until the manifestation of the first-activated (hypomanic or manic) episode; however, the classical disorder almost always starts with depressive episodes. 49 Moreover, depressive episodes typically antecede the first diagnosable activated episode by many years.…”
Section: 26mentioning
confidence: 99%
“…More recently, two review articles on bipolar offspring reported elevated but varying prevalence rates of bipolar disorder (ranging from 3% to 27%), mood disorders (ranging from 5% to 67%), and non-mood disorders (ranging from 5% to 52%) (2,3). However, these studies could not fully address the development and early course of bipolar disorder and other mood disorders because they used either a crosssectional design or a longitudinal design without follow-up into adulthood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We report here on one of the largest prospective bipolar offspring studies with a follow-up into adulthood: the 12-year follow-up of the Dutch bipolar offspring cohort (7,10,12).…”
mentioning
confidence: 99%